Diagnóstico de tuberculose em bovinos leiteiros - Dametto, Leonardo Luiz (2018)
Tuberculosis is a chronic anthropozoonosis of worldwide occurrence, whose etiological agent belongs to the genus Mycobacterium. In animals, the disease generates great economic damages to the productive chain of meat and milk. The human infection occurs mainly through direct contact with contaminated animals and by the ingestion of raw milk and derivatives made from raw milk, such as cheeses. In Brazil, there is the National Program for the Control and Eradication of Brucellosis and Tuberculosis, as well as the Sanitary Inspection Service and Sanitary Surveillance, which establish measures and criteria to protect animal and public health. However, the greatest challenge for the control of human tuberculosis is in the population's awareness of the risks of infection when purchasing meat or raw milk and its derivatives, such as cheeses, directly from producers, fairs and / or outdoors, without control hygienic-sanitary and inspection. The present work describes the use of four tools for the diagnosis of mycobacteria, including the comparative cervical tuberculin test, macroscopic findings during sanitary slaughter, histopathology of injured tissues followed by histochemistry. The study evaluated a total of 211 dairy cattle, where 74 (35%) showed reactivity in the comparative cervical tuberculin test, considering the positive and inconclusive results. Of the total number of animals, 143 (67,8%) were referred for sanitary slaughter due to legal and control issues in the foci of the disease. In the follow up of slaughtering and inspection of viscera and carcasses, 74 (51,8%) had macroscopic lesions compatible with bovine tuberculosis, while 69 (48,2%) showed no visible changes. During the inspection tissue samples were collected from five tuberculin-positive bovines with macroscopic lesions and five tuberculin-positive without lesions. In the histopathological analysis, all of them presented numerous areas of caseous necrosis and chronic inflammatory reaction with or without central calcification and in the special staining of Ziehl-Neelsen, numerous alcohol-acid resistant bacilli were evidenced in all the cases examined. Thus, given the results obtained, the four analysis tools used in the present study proved to be very useful for the definitive diagnosis of bovine tuberculosis. The findings in the dairy herd also showed that the disease is circulating among this category of animals, posing a serious threat to the other cattle, to humans that come in direct contact with these cattle and / or who consume or handle infected animal products.